Fertility decline in Ghana: Implications for public policy - Gaisie, S.K. (Population, Health and Development in Ghana: Attaining the Millennium Development Goals, 2007)
2 Chapter Fertility Decline in Ghana: Implications for Public Policy S. K. Gaisie Introduction The population of Ghana has undergone a structural transformation since the beginning of the fertility decline in the late 1980s. Accompanying the decline are a number of issues that need to be investigated or researched into in order to assess their demographic, social, political and economic impact. Sample surveys (i.e. 1960 Post-Enumeration Survey, 1968/69 Demographic Sample Survey and 1971 Supplementary Inquiry) provided the information required for determination of the level of fertility in the 1960s and 1970s. All the estimates of the total fertility rates indicated that the country’s fertility was high and stable, lying in the neighbourhood of between 6.7 and 7 children per woman. A total fertility rate of 6.9 children per woman appeared to be the most plausible estimate (Gaisie, 1969; 1974; Gaisie and deGraft Johnson, 1976). Estimates based on the 1979/1980 Ghana Fertility Survey (GHS) data indicate that total fertility rate for the period 1960s to mid-1970s ranged between 6.85 and 6.99 children per woman. Evaluation and adjustment of the data for the recent period (1975-1980) yielded a total fertility rate of 6.69 as compared with the reported one of 6.47 (Gaisie, 2005). All told, the estimates derived from the data sets spanning a period of more than 25 years show that the level of fertility was high and stable during the 1960s, 1970s and early 1980s. The reported total fertility rates derived from the 1993, 1998 and 2003 Demographic and Health Surveys data indicate a significant and steady fertility decline since then; falling from 6.43 in 1988 to 5.50 in 1993, 4.55 in 1998 and then to 4.44 in 2003. However, the need to detect and measure trends in fertility with accuracy and sensitivity in a society that is experiencing population expansion is crucial for competent planning. For instance, plausible fertility estimates based on reliable data are critical for construction of population projections as well as for monitoring and evaluating action programmes for reducing the rate of growth via family limitation. A number of estimation procedures and strategies were therefore employed to derive plausible estimates of fertility levels and trends during the transition period. The results are presented elsewhere (Gaisie, 2005). Substantive issues and their implications are the subject-matter of this chapter. Quantum and Pace of Decline Three estimation procedures yielded estimates which suggest that the level of fertility in Ghana fell from about seven children per woman in the 1960s and 1970s to 4.6 children per woman by the turn of the last century; a decline of 33% during the 43 year period (1960-2000) or an annual decline of 0.8% as depicted in Figure 1. The average number of children born to a Ghanaian woman was reduced by 2.3 children; a reduction of 0.05 children per year during the entire period. The pace of the decline, however, increased to 0.2 children per year during the late 1980s and the 1990s and slowed down considerably to 0.04 children per year by the beginning of the 21st century with the total fertility rate falling from 4.8 in the late 1990s to 4.6. The change was much more marked among the younger women (20-35-year olds) 14 POPULATION, HEALTH AND DEVELOPMENT than among the older cohorts, particularly during the second half of the 1990s. However, the decline appears to have stalled. Figure 1. Total Fertility Rate: 1960-2003 Fertility Decline and High Rate of Growth Fertility trends affect the rate of growth by determining the number of births women have, and the size of the different generations. In a majority of the African countries where fertility is above replacement level, children outnumber their parents by substantial amounts and the children in turn have more children than required to replace their parents’ generations even when fertility level is declining (Table1). Consequently, as fertility falls, the number of births to relatively large generations of parents is higher for some time than the number of deaths in the population, most of which are that of grand parents and great grand-parents. This process tends to maintain a relatively high positive population growth rate even though fertility is falling. In most of the countries where fertility rate is reported to be falling, overall population growth rates are relatively high, implying that fertility rate is still high and in consequence...